Extraction And Characterization Of Pig Skin Gelatin Compared To Commercial Porcine Gelatin - Mishra, Bidyut Prava; Lalthanmawii, Judy; Reddy, P Sowmya; Mounika, T; Dasoja, Sowmya; Belore, Balaji M; Prasad, M G; Nath, D Narendra; Rao, T Srinivasa; Mallika, E Naga; Banerjee, Rituparna; Rao, B Eswara; et al. (Journal of Meat Science, 2023)
A study was conducted to extract gelatin from pig skin and to evaluate and compare its physicochemical properties with those of commercial porcine gelatin. Whitish yellow-colored gelatin powder was extracted from pig skin through acetic acid pre-treatment, heating, filltration and drying steps. The average yield of pig skin gelatin (PSG) was 5.98 % (w/w). The protein, moisture, fat and ash content of PSG were 90.24, 8.13, 0.60 and 0. 56 %, respectively. The gel (6.67%) prepared from PSG showed a transmittance of 24.71 % and a pH of 6.45. The electrophoretic pattern of the gelatin samples showed the presence of both α1 and α2 chains with the highest molecular weight band observed at around ~ 200 kDa.  The L*, a*, and b* values of PSG were recorded as 79.28, 0.58 and 5.79, respectively. Compared to commercial porcine gelatin, PSG had lower hydroxyproline content but a higher pH (p < 0.05) value. Our findings suggest that good quality gelatin with optimal properties can be extracted from low-value pig skin which can provide a suitable alternative to traditional gelatin derived from pork bones or beef bones and skin.
Keywords: Gelatin; Pig skin; Hydroxyproline content; Proximate composition; Colour